2016
DOI: 10.1007/s00521-016-2325-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-source deep transfer learning for cross-sensor biometrics

Abstract: Deep transfer learning emerged as a new paradigm in machine learning in which a deep model is trained on a source task and the knowledge acquired is then totally or partially transferred to help in solving a target task. In this paper, we apply the source-target-source methodology, both in its original form and an extended multi-source version, to the problem of cross-sensor biometric recognition. We tested the proposed methodology on the publicly available CSIP image database, achieving state-of-the-art resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, apart from the deep learning methods, we also show the comparison with handcrafted features such as Histogram of Oriented Gradients (HOG) [6] and Daisy features (similar to SIFT) [33]. The 1 Kandaswamy et al [12] has reported results on this database, but the protocol used in their work is transfer learning based. Santos et al [27] had performed cross-sensor experiments, but evaluated their algorithm on the entire dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, apart from the deep learning methods, we also show the comparison with handcrafted features such as Histogram of Oriented Gradients (HOG) [6] and Daisy features (similar to SIFT) [33]. The 1 Kandaswamy et al [12] has reported results on this database, but the protocol used in their work is transfer learning based. Santos et al [27] had performed cross-sensor experiments, but evaluated their algorithm on the entire dataset.…”
Section: Resultsmentioning
confidence: 99%
“…A possible alternative is to use deep transfer learning (DTL) which offers more flexibility when extracting high-level features [41]. DTL can perform layer-by-layer feature transference to solve a target problem in either a supervised or unsupervised setting [80]. -In a CNN, the features detected by earlier layers include low-level image details such as edges and colors.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, some related works are briefly introduced. Examples of applications in different research areas, such as image classification [ 48 , 49 ], text classification [ 50 ], and biometrics [ 51 ], can be found in the literature. In Reference [ 52 ], a new multi-source deep transfer neural network algorithm, based on a convolutional neural network (CNN) and a multi-source TL technique, is proposed and evaluated on several classification benchmarks.…”
Section: Related Workmentioning
confidence: 99%